My journey into the heart of terror ten days in the Islamic State - Todenhofer, Jurgen (Greystone Books, 2016)
The German journalist documents his ten days in the Islamic State, a time during which he interviewed fighters in Mosul to consider their point of view to better understand the ways to combat their fundamentalism.